Genome Sequencing of Amomum tsao-ko Provides Novel Insight Into Its Volatile Component Biosynthesis - Sun, Fenghui; Yan, Chaochao; Lv, Yunyun; Pu, Zhonghui; Liao, Zedong; Guo, Wei; Dai, Min (Frontiers in Plant Science, 2022)
As an important economic and medicinal crop, Amomum tsao-ko is rich in volatile oils and is widely used in food additives, essential oils, and traditional Chinese medicine. However, the lack of a reference genome remains a limiting factor for understanding the molecular basis of its medicinal properties. Here, we assembled the genome of Amomum tsao-ko using 288.7 Gb of PacBio long reads and 105.5 Gb of Illumina short paired-end reads. The genome was 2.70 Gb in size with a contig N50 of 2.45 Mb. Approximately 90.07% of the predicted genes were annotated in public databases. Based on comparative genomic analysis, genes involved in secondary metabolite biosynthesis, flavonoid metabolism, and terpenoid biosynthesis showed significant expansion. Notably, the DXS, GGPPS, and CYP450 genes, which participate in rate-limiting steps for terpenoid backbone biosynthesis and modification, may be the key genetic basis for essential oil formation in A. tsao-ko. The A. tsao-ko reference genome provides a valuable genetic resource for understanding the unique features of this plant and for further evolutionary and agronomic studies of Zingiberaceae species.